Epidemiological, clinical and surgical features in patients with ectopic pregnancy at Hospital Nacional Arzobispo Loayza - Guadalupe, Ángel Iván Martínez (2013)
Objectives: To describe the epidemiological, clinical and surgical features of ectopic pregnancy. Design: Descriptive, retrospective study. Setting: Department of Obstetrics and Gynecology, Hospital Nacional Arzobispo Loayza, Lima, Peru. Participants: Patients with ectopic pregnancy. Interventions: Medical records of 348 patients with final diagnosis of ectopic pregnancy during 2006- 2010 were reviewed. Main outcome measures: Characteristics of women with ectopic pregnancy. Results: There was a frequency of one ectopic pregnancy for every 49 births. Mean age was 29.2 ± 6.5 years; unmarried patients accounted for 28.5%; 65.6% had more than one sexual partner and 25.9% were nulliparous; 25.9% presented a history of either uterine curettage or manual vacuum aspiration; 54.3% had sex during menstrual periods, 22.1% suffered of pelvic inflammatory disease and 33.8% used intrauterine device for birth control. Average time of amenorrhea was 6.8 ± 2.1 weeks. Main symptom was abdominal pain (97.9%). Transvaginal ultrasonography showed adnexal mass in 70.7% of cases. Over 60% were resolved in less than 6 hours. Surgery was performed in 94.8%, 4% had medical treatment and 1.2% expectant management. Total salpingectomy (67.6%) was the main type of procedure performed. The most common location was tubal (94.5%), especially in the ampullary region. Conclusions: The frequency of ectopic pregnancy was higher than in other local studies. Patients admitted with diagnosis of ectopic pregnancy usually came late, presenting complications that required surgical management often radical in the emergency service. Keywords: Ectopic pregnancy, risk factors, diagnosis, management,salpingectomy.